Comparative studies of temperature fluctuations within wooden and steel silos in Ibadan (1997)
Temperature fluctuations and moisture condensation within the interiors of a steel and wooden silos were determined experimentally. The steel silo is of 1mm thickness while the wooden silo is a two-layered wall panel of 12mm and 6mm thick plywood separated by 50mm air-gap. Measurements taken during the hotter months of March and April in Ibadan showed that temperature fluctuations in the steel and wooden silos were 9°C and 7°C respectively. Corresponding maximum temperature in the silos were 38.5°C and 37.2°C. While the interior of the wooden silo remained dry, the steel silo had condensed moisture droplets lining its inner walls. Since moisture condensation in a silo contributes to grain spoilage by biological agents, wooden silos are rated superior in respect of reducing this adverse feature.